A defense of the hypothesis of massive modularity based on Carruthers and Crawford according to the theoretical foundations of modern evolutionary psychology - Cruzado Torre, Mike Christian (2021)
Evolutionary Psychology (EP) supports the hypothesis of massive modularity (HMM), in which the mind is understood as a set of modules that fulfill a specific function to solve recurrent adaptive problems in our evolutionary adaptation environment. This set would be part of human nature and the objective of EP is to identify and explain them in distal terms. Its detractors argue that the modular conception is inconsistent with current theoretical and empirical knowledge. From the works of Carruthers and Crawford, I will defend that several of the criticisms against HMM assume the modular conception of Fodor (F-modules), who emphasizes the intentional aspect. However, EP highlights biological functionality, conceives modules as adaptive traits that evolve due to their effects on differential reproduction; that is, Darwinian modules (D-modules) and understands them as specialized information processing systems. This gives a different nuance to the innate and encapsulated of the modular conception, so the theoretical and empirical implications and assumptions also vary. Finally, clarifying these conceptual confusions and providing factual evidence, it is concluded that the HMM is epistemologically viable.